Fourier transform infrared (FT-IR) study on cyanide induced biochemical and structural changes in rat sperm. (2015) - Shivanoor, Shiddappa Mallappa; David, Muniswamy
Highlights: Lower doses of cyanide did not alter the biochemical compositions in rat sperms. Higher doses of cyanide had induced significant decrease in biochemical compositions in rat sperms. Cyanide induced alterations in secondary structure of proteins present in rat sperms. FT-IR spectroscopy is a powerful tool used to investigate oxidative damage in sperms. Abstract: In the recent years, great attention had been focused on cyanide toxicity because of its widespread use in industries and considered to be a ubiquitous pollutant in the environment. Therefore, the current study aimed to evaluate the toxic effect of cyanide on rat sperms at molecular level by using FT-IR technique. For this purpose, rats were randomly divided into four groups and treated with 0.0, 0.64, 1.2 and 3.2 mg kg −1 body weight (BW) for the period of 90 days. The group treated with lower dose (0.64 mg kg −1 BW) showed an insignificant change in all the peaks, except the peaks assigned to olefinic CH, CH2 asymmetric and CH2 symmetric stretching vibration in the lipids. While, the groups treated with higher doses (1.2 and 3.2 mg kg −1 BW) showed the significant decrease in the area under the peaks corresponds to different bio-molecules. In addition, spectral second derivative analysis showed the significant alteration in α-helix, turns, β-sheet, aggregated β-sheet and random coil structures in the proteins. In conclusion, the selected higher dosage of cyanide had caused significant decrease in the biochemical composition of rat sperms along with structural changes in the proteins. The FT-IR technique is an excellent tool used for the analysis of oxidative damage in the sperms.